KARKTERISTIK CAMPURAN BETON ASPAL (AC-WC) DENGAN MENGGUNAKAN VARIASI KADAR FILLER LIMBAH ABU TERBANG BATUBARA - Fahmi, Ahmad K.A; Qomariah; Yunaefi (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2021)
Asphalt is a very important pavement material and is often used in road construction in Indonesia. Laston AC-WC is a mixture of highway pavement which is located at the top which is directly related to the vehicle's axle. As for some components of asphalt mixture, namely: (1) asphalt (2) aggregate (3) filler. One component of asphalt concrete that will be replaced is filler. This filler functions as an enhancer of stability and reduces air cavity. In this case coal ash / fly ash instead of filler components is expected to be a solution to get good quality and cheap prices, considering coal ash / fly ash is very easy to obtain and the price is relatively cheap so it is necessary to choose asphalt mixture using fly ash as a filler to test its characteristics. In this study the authors aim to find: (1) the chemical content of fly ash (2) how much influence the fly ash has on concrete asphalt mixtures with filler content variations of 0%, 25%, and 50%, (3) optimum levels of asphalt with fly substitution ash, (4) estimated cost of implementing asphalt concrete mix with fly ash substitution. This research was conducted in the Malang State Polytechnic laboratory. In the study the authors used 10 sample specimens, with an average diameter of 10 and an average height of 6.85 with variations of asphalt, 4.5%, 5%, 5.5%, 6%, 6.5%. From the testing specimens take 24 hours, before the test specimens were tested using the Marshall method. The results of testing the characteristics of Marshall with non-substitutes get 5.25% KAO with VMA value: 22.00%, VIM: 4.62%, Stability: 851.69kg, Flow: 3.21%. This KAO value is used as a reference to look for KAO with 25% and 50% fly ash substitution. Marshall characteristic test results with 25% fly ash substitution get VMA values: 23.37%, VIM: 3.97%, Stability: 595.38kg, Flow: 4.54%. And testing the characteristics of Marshall with 25% fly ash substitution got a VMA value: 21.17%, VIM: 3.79%, Stability: 561.08kg, Flow: 4.59%. And the cheapest cost estimate is owned by Laston AC-WC with a 50% substitution at a price of Rp 5.616.136.446